Road to Disunion, Volume I : Secessionists at Bay, 1776-1854. - Freehling, William W. (Oxford University Press, USA, 1990)
Far from a monolithic block of diehard slave states, the antebellum South was, in William Freehling's words, ""a world so lushly various as to be a storyteller's dream."" It was a world where Deep South cotton planters clashed with South Carolina rice growers, as Northern egalitarianism infiltrated border states already bitterly divided on key issues. It was the world of Jefferson Davis, John C. Calhoun, Andrew Jackson, and Thomas Jefferson, and also of Gullah Jack, Nat Turner, and Frederick Douglass. Now, in the first volume of his long awaited, monumental study of the South's road to disunio.